Axial Calibration of QPD Signal based on Stuck Bead Method for Optical Trapping Applications - Yusof, Mohd Farid Mohamad; Yeng, , Muhamad Safuan Mat; Ayop, Shahrul Kadri (International Journal of Engineering and Technology, 2018)
Calibration of axial quadrant photodetector (QPD) signal to the trapped bead position in an optical tweezer is important to measure the quantitative mechanical parameter in axial (laser propagation) direction. An alternative calibration based on the Stuck Bead Method (SBM) was proposed in this study. 3 Âµm polystyrene beads were stuck at the surface of glass coverslip and moved axially around the laser focus. QPD was used to obtain the position dependent intensity profile at three different laser powers (19.8 mW, 34.1 mW, 48.5 mW). The QPD signal-to-distance calibration value was consistent at 26 mV/Âµm for the used bead at the three laser powers. It was found that the calibration values are independent of laser powers and limited by the resolution of distance adjustment.